Tracing CO₂ emissions in global value chains: Multinationals vs. domestically-owned firms - Meng Li; Bo Meng; Yuning Gao; Zhi Wang; Yaxiong Zhang; Yongping Sun (Research Network Sustainable Global Supply Chains, 2022)
This study integrates the new global value chain (GVC) accounting method that explicitly considers the difference in the production functions of multinational enterprises (MNEs) and domestically-owned firms into existing production- and consumption-based CO2 emissions measures. This enables us to consistently trace emissions in GVCs through trade- and foreign direct investment (FDI)-related routes at the bilateral country-sector level by firm ownership. Based on OECD data, our empirical results, reveal that emissions related to FDI account for 15.2 percent of the world's total emissions and 58.1 percent of the world's GVCs emissions, 39.2 percent of which are emissions related to FDI for foreign demands in 2015. From 2000 to 2015, south-south emission transfers experienced rapid growth with relatively high carbon intensity. MNEs play a significant role through FDI in south countries, both in generating emissions as energy users and in transferring emissions as high-carbon intensive intermediate goods users in GVCs. There is a substantial difference in the patterns of emissions creation, transfer, and absorption in GVCs by firm ownership. These findings help us to better understand who creates emissions for whom and from which route and their potential environmental responsibility along GVCs.
Keywords: Q54; C67; F64; 330; embodied carbon emissions; carbon footprint; global value chain; multinational enterprises; emission responsibility; GVC; FDI